2014
DOI: 10.1159/000363232
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Disorders in Opioid Maintenance Therapy: Prevalence, Clinical Correlates and Treatment

Abstract: Maintenance therapy with methadone or buprenorphine is an established and first-line treatment for opioid dependence. Clinical studies indicate that about a third of patients in opioid maintenance therapy show increased alcohol consumption and alcohol use disorders. Comorbid alcohol use disorders have been identified as a risk factor for clinical outcome and can cause poor physical and mental health, including liver disorders, noncompliance, social deterioration and increased mortality risk. The effects of opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 112 publications
6
61
2
Order By: Relevance
“…Such findings are consistent with previous research [24]. Although stimulants (cocaine), and other drugs, including cannabis and benzodiazepines, have been previously found to be potential predictors of changes in alcohol consumption [5], our research confirmed this for cannabis only. Irrespective of the reasons for heavy drinking, our study confirmed a high prevalence of this problem (32%); therefore, the national guidelines and policies should give clear guidance about the management of concurrent heavy drinking among this population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Such findings are consistent with previous research [24]. Although stimulants (cocaine), and other drugs, including cannabis and benzodiazepines, have been previously found to be potential predictors of changes in alcohol consumption [5], our research confirmed this for cannabis only. Irrespective of the reasons for heavy drinking, our study confirmed a high prevalence of this problem (32%); therefore, the national guidelines and policies should give clear guidance about the management of concurrent heavy drinking among this population.…”
Section: Discussionsupporting
confidence: 93%
“…Methadone maintenance therapy (MMT) has been shown to reduce morbidity and mortality among people who use heroin and other opiates [3,4]; however, previous studies have suggested a high prevalence of heavy alcohol use among MMT patients [5-7], and interventions to reduce heavy drinking in this population are lacking [8]. MMT patients who engage in heavy alcohol use do not appear to benefit from MMT to the same extent as those who do not, and most of them develop further complications [9-11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polydrug use remains a major concern in these patients. The relatively high number of individuals with alcohol use found in this study corresponds to similar findings in other studies (for review see [38]).…”
Section: Discussionsupporting
confidence: 92%
“…The rate of patients with suspected alcohol related problems is in the range of those reported for untreated heroin users, for patients entering OMT, or for OMT patients with mixed treatment durations (Soyka, 2015). In the German general population, alcohol abuse or dependence has a 7.5% prevalence rate in males, and 2% in females (Jacobi et al, 2014); there is some evidence, though, that the rate of alcohol use disorders in opiate dependents is not significantly higher than in the general population with similar socioeconomic characteristics (Ottomanelli, 1999).…”
Section: Discussionmentioning
confidence: 97%